Employee reactions to CSR in the pursuit of meaningful work: A case study of the healthcare industry - Janssen, Josine L.; Lysova, Evgenia I.; Wickert, Christopher; Khapova, Svetlana N. (Frontiers in Psychology, 2022)
With the growing interest in the microfoundations of corporate social responsibility (‘micro-CSR’), many questions linger regarding how the workforce reacts to CSR, which has consequences for their meaningful work experiences. To address this lack of understanding, we conducted an inductive, comparative case study of two healthcare organisations to examine how employees experience meaningful work through reacting to their organisation’s CSR initiatives. We demonstrate how CSR triggers employees’ meaning-making of work, which takes the form of a misalignment perceived between CSR at the strategic-level and CSR as it is implemented at the employee-level, limiting the experiences of meaningful work. We identify four proactive behaviours in which employees engage to infuse their work with meaning as a way of dealing with this experienced mismatch. We consolidate these behaviours into a typology of meaning-infusing behaviours in the context of CSR in healthcare. Specifically, we found that when guided by the need for making a positive impact on their beneficiaries, employees engage in what we call ‘reshaping work for impact’ next to ‘collective enabling of impact’. In contrast, when guided by the need for having a sense of meaningful membership, employees are guided by either ‘creating a sense of belonging’ or ‘envisioning prosocial potential’. Through these behaviours, they either navigate within given organisational structures or enact new ones. Overall, we expand research on the CSR–meaningful work relationship, emphasising the role of employees’ proactive behaviours in understanding their experiences and reactions to CSR initiatives in their pursuit of meaningful work. Moreover, we highlight implications for micro-CSR research and practice.